2018
DOI: 10.12659/msm.909943
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Nottingham Hip Fracture Score in Different Health Systems and a New Modified Version Validated to the Greek Population

Abstract: BackgroundThe Nottingham Hip Fracture Score (NHFS) is validated as a predictive mortality tool in patients with hip fracture. However, it has not been modified or validated widely other than in the UK NHS health systems.Material/MethodsWe assessed the predictive capability of the NHFS for 30-day mortality after surgery for hip fracture in the Greek population and then compared the original model to a modified one. We applied the NHFS to the Greek population and created a modified model of the NHFS by including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
0
21
0
2
Order By: Relevance
“…In Greece, most elderly adults live at home, supported by family members. 2 , 11 , 19 For this reason, Tilkeridis et al replaced the factor of institutionalization with the New Mobility Score to calculate the NHFS; however, this version of the NHFS was not validated externally. 19 Similar adjustments to the NHFS have been made to develop new prediction tools, such as the Almelo Hip Fracture Score proposed by Nijmeijer et al 3 However, their also had observed events included in the model (64 events in a population of 850 patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Greece, most elderly adults live at home, supported by family members. 2 , 11 , 19 For this reason, Tilkeridis et al replaced the factor of institutionalization with the New Mobility Score to calculate the NHFS; however, this version of the NHFS was not validated externally. 19 Similar adjustments to the NHFS have been made to develop new prediction tools, such as the Almelo Hip Fracture Score proposed by Nijmeijer et al 3 However, their also had observed events included in the model (64 events in a population of 850 patients).…”
Section: Discussionmentioning
confidence: 99%
“…For validation of the NHFS, the outcome measure of interest is 30-day 10 For external validation of a model, a number of statistical principles apply: validation is done in a fully different setting than that in which the development was done, 15 the minimum number of observed events in the study cohort is 100; 15,16 , and the variable of interest has similar incidence or prevalence in both development and validation cohorts. 17 Three validation studies have been in conflict with these statistical principles: by Kau et al, Tilkeridis et al, and Karres et al 10,18,19 These studies were not compliant with the minimum required observed events, reporting 15 (7.3% mortality in a sample of 212), 33 (9.5% mortality in a sample of 349), and 89 events (8.2% mortality in a sample of 1,050), respectively. Kau et al, however, found that the NHFS accurately predicted 30-day mortality for surgically treated hip-fracture patients.…”
Section: Discussionmentioning
confidence: 99%
“…NHFS is mostly studied in England, but investigations attempting validation of the score have been performed in Sweden, Scotland, Singapore, Netherlands and Greece 6,18,19 . Several studies have modified the system to accommodate for local practices.…”
Section: Discussionmentioning
confidence: 99%
“…Για το έτος 2025 υπολογίζεται ότι για τις ηλικίες 50-74 θα φτάσουν τα 5.207 κατάγματα και για τις ηλικίες 75+ θα φτάσουν τα 13.539 κατάγματα (Svedbom et al, 2013). Η συχνότητα των καταγμάτων ισχίου αυξήθηκε από 107,3/100.000 κάτοικους πριν το 1992 σε 118,6/100.000 κατοίκους το 1997, ενώ η αύξηση αυτή οφειλόταν κυρίως στη γήρανση (Karagiannis et al, 2006;Paspati et al, 1998 (Tilkeridis et al, 2018).…”
Section: κατάγματα ισχίουunclassified
“…Μέχρι σήμερα λίγες μελέτες έχουν ερευνήσει το κάταγμα ισχίου κυρίως σε σχέση με τις κοινωνικο-οικονομικές συνθήκες (Bugeja et al, 2018;Johansson et al, 2018;Reyes et al, 2015;Quah et al, 2011), ενώ και η χρήση των ΓΠΣ είναι περιορισμένη στο πεδίο των πτώσεων και των τραυματισμών (Bamzar & Ceccato, 2015;Towne et al, 2015;Morency et al, 2012;Lai et al, 2011;Turner et al, 2009;Lai et al, 2009). Ιδιαιτέρως στην Ελλάδα όπου δεν υπάρχει Εθνική Βάση Κατάγματος Ισχίου (Tilkeridis et al, 2018), οι περισσότερες μελέτες κυρίως επιδημιολογικές προσεγγίζουν το κάταγμα σε σχέση με την οστεοπόρωση, τη σύγκριση διαφορετικών τεχνικών χειρουργικής αντιμετώπισης, τη λειτουργικότητα και τη θνησιμότητα (Makridis et al, 2015;Svedbom et al, 2013;Lyritis et al, 2013;Dailiana et al, 2013;Papakonstantinou et al, 2008;Karagiannis et al, 2006 Ravindran & Kutty, 2016;Jha et al, 2010;Grisso et al, 1991). Η επιλογή των μαρτύρων από τον γενικό πληθυσμό έχει προταθεί από τους Grisso et al (1991) (Grisso et al, 1991 (Franse et al, 2017;Vieira et al, 2016;Keal et al, 2015;Grisso et al, 1991 (Lin et al, 2018;Curtis et al, 2016;Gale et al, 2016;Stewart Williams et al, 2015;Taylor et al, 2011;Wilson et al, 2006).…”
Section: ερευνητικά εργαλείαunclassified